2021
DOI: 10.1055/a-1482-8840
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of undiagnosed diabetes mellitus among gastroenterological patients: a HbA1c-based single center experience – Prevalence of undiagnosed diabetes in gastroenterological patients

Abstract: Background Diabetes mellitus is a major risk factor for microvascular disease, leading to chronic kidney injury or cardiovascular disease, but there is a tremendous proportion of patients worldwide who suffer from undiagnosed diabetes. Until now, little is known about the prevalence of undiagnosed diabetes in gastroenterology inpatients. Objective To improve detection of undiagnosed diabetes, a routine screening procedure for gastroenterology inpatients, based on hemoglobin A1c (HbA1c) and fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Attention to possible glucose impairments in PSC patients was supported by the finding of Fründt et al [80] who found an increased risk of having undiagnosed diabetes (based on HbA1c and fasting glucose values) in PSCrelated liver cirrhosis, while patients having cirrhosis due to another aetiology did not.…”
Section: Diabetes In Patients With Primary Sclerosing Cholangitismentioning
confidence: 92%
“…Attention to possible glucose impairments in PSC patients was supported by the finding of Fründt et al [80] who found an increased risk of having undiagnosed diabetes (based on HbA1c and fasting glucose values) in PSCrelated liver cirrhosis, while patients having cirrhosis due to another aetiology did not.…”
Section: Diabetes In Patients With Primary Sclerosing Cholangitismentioning
confidence: 92%